2004
DOI: 10.1152/japplphysiol.01278.2003
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-binding proteins and lipoprotein lipase activity in human skeletal muscle: influence of physical activity and gender

Abstract: The protein and mRNA levels of several muscle lipid-binding proteins and the activity and mRNA level of muscle lipoprotein lipase (mLPL) were investigated in healthy, nonobese, nontrained (NT), moderately trained, and endurance-trained (ET) women and men. FAT/CD36 protein level was 49% higher (P < 0.05) in women than in men, irrespective of training status, whereas FAT/CD36 mRNA was only higher (P < 0.05) in women than in men in NT subjects (85%). Plasma membrane-bound fatty acid binding protein (FABPpm) conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
149
2
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(174 citation statements)
references
References 63 publications
19
149
2
4
Order By: Relevance
“…Increased lipoprotein lipase activity in obesity may facilitate intramyocellular FFA content and, secondary to this, IMTG content. A two-to threefold greater lipoprotein lipase gene expression in skeletal muscle has been demonstrated in sedentary women compared to sedentary men and may indicate an increased potential for increasing muscular lipoprotein activity in females (14). A gender difference in IMTG may also be caused, at least in part, by sex related differences in hormone sensitive lipase activity in the muscle (15).…”
Section: Introductionmentioning
confidence: 99%
“…Increased lipoprotein lipase activity in obesity may facilitate intramyocellular FFA content and, secondary to this, IMTG content. A two-to threefold greater lipoprotein lipase gene expression in skeletal muscle has been demonstrated in sedentary women compared to sedentary men and may indicate an increased potential for increasing muscular lipoprotein activity in females (14). A gender difference in IMTG may also be caused, at least in part, by sex related differences in hormone sensitive lipase activity in the muscle (15).…”
Section: Introductionmentioning
confidence: 99%
“…O ciclo menstrual parece influenciar a utilização de carboidratos nas mulheres durante o exercício 29 , mas não altera o metabolismo de lipídeos 30 . É importante observar que a maioria dos estudos vem comparando homens e mulheres, quando estas estão na fase folicular do período menstrual (momento em que as concentrações de 17β-estradiol estão relativamente baixas) [2][3][4]7,12,13,15,20,[31][32][33][34] . As diferenças entre os sexos podem ser maiores quando as mulheres são avaliadas na fase luteal do ciclo menstrual 23 .…”
Section: N T R O D U ç ã Ounclassified
“…Posteriormente, Kiens et al 32 avaliaram de que forma a atividade física e sexo influenciam o metabolismo lipídico em relação à lipoproteína lipase muscular (mLPL) e às proteínas ligantes de lipídeos, em indivíduos realizando exercício em bicicleta a 60% de VO 2MÁX , durante 90 minutos. Participaram 24 mulheres, na fase folicular do ciclo menstrual, e 22 homens de diferentes capacidades aeróbicas (não-treinados, moderadamente treinados e atletas de endurance).…”
Section: Diferenças Na Utilização De Lipídeosunclassified
“…Nevertheless, changes do occur: neither dramatic nor unequivocal, but interesting changes can be observed. According to the literature, when isolating VLDL from total serum TG, some authors found a more significant muscle uptake of circulating VLDL during exercise in humans and rodents [3] and [4]. Moreover, it was shown that the turnover rate of VLDL is significantly higher during exercise than at rest [5].…”
Section: Introductionmentioning
confidence: 99%